Developing a Medical Garment for Upper-Body Posture-Related Issues - R.A.H.S. Ranawaka; S.D.M.W. Kularatne; E.A.S.K. Fernando; S.N. Niles; T.S.S. Jayawardane; R.K.P.S. Ranaweera (Tekstilec)
The increase in incorrect posture in the daily lifestyle of many individuals has led to numerous issues. Of these, lower back pain is recognized as the most common posture-related medical condition. Existing effective solutions for posture-related issues are complex to use, and are diverse in nature, ranging from the identification of the problem to the correction of posture. In this research, an attempt was made to provide an effective solution in the form of a short sleeve undershirt with carefully designed extensible structures matching the required reinforcement for different segments of the spine. The additional functionality of the proposed garment was verified through proper scientific testing using sEMG. The correction mechanism utilizes a combination of sensory tension applied to the wearer and the reinforcement of the spine with a specially made backbone structure attached to a custom-made garment. Woven narrow bands and warp knitted fabrics were used in the garment. The backbone structure is strategically placed on the garment to control the specific muscles related to correct postural balance. It was found that the garment reduces the activation of certain back muscles and promotes voluntary posture correction.